Yield ratios of the isomeric pair Ce 137 m137 formed by La 139 (d,4n) Ce 137 reaction - Vignau, H.; Jorge Nassif, Sonia (North Holland Publishing, 1961)
Fil: Vignau, H. Comisión Nacional de Energía Atómica; Argentina